Influence of reef structure and its flow field effect on the spatial behavior of Sebastes schlegelii adults - Gong, Pihai; Li, Jiao; Wang, Gang; Guan, Changtao; Meng, Zhen; Jia, Yudong (Frontiers in Marine Science, 2023)
Sebases schlegelii is an important economic reef fish in northern China. Its distribution in the reef area is affected by the reef structure and flow field. To evaluate the effects of differently shaped artificial reefs with distinct flow field properties on the distribution of adult S. schlegelii, four types of artificial reefs (cubic (CAR), pyramidal (PAR), star-shaped (SAR) and tubular (TAR) artificial reef) and the related flow regimes were experimentally examined. The mean gathering rate (MGR) and wavelet analysis were adopted to analyze the distribution patterns of S. schlegelii adults around reef bodies in three representative environmental conditions (static water (FE1), 40 Hz water flow environment (FE2), and 50 Hz water flow environment (FE3)). The significant gathering behaviors around the artificial reefs were depicted through the MGR of adult fish during physical observations. For FE1, the MGR of adult fish showed a decrease in the order PAR > CAR > SAR > TAR. With increasing incoming velocities, the MGR changed such that the quantity of adult fish in the CAR gradually increased more than that in the PAR, but no significant differences were observed between them (P>0.05). Wavelet analysis showed that the fluctuations in the gathering behaviors of adults decreased with increasing flow velocities. Based on the two-factor analysis of variance, the reef structural characteristics had a more significant impact than the flow velocities on the gathering behavior of adult fish. In summary, the PAR and CAR are recommended to restore the habitats of S. schlegelii in marine ranches given their dominant aggregation effects on S. schlegelii.